A method for preparing high-purity magnesium sulfate

By forming graphene on polyimide sheets and adsorbing impurities, combined with grinding, calcining and immersion of magnesium chloride solution, the problem of low purity when preparing magnesium sulfate is solved, and the preparation of high-purity magnesium sulfate is achieved.

CN119143160BActive Publication Date: 2025-02-11LAIZHOU LAIYU CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411597256.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-11
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

In the prior art, magnesium sulfate prepared with dolomite as raw material contains impurities such as calcium and iron, and has a low purity and cannot meet the high purity needs of downstream industries.

Method used

Laser treatment is used to generate graphene on polyimide sheets, which is used to adsorb impurities in the preparation of magnesium sulfate. The carbonate components in dolomite are decomposed by grinding, calcining and immersion of magnesium chloride solution to remove some impurities. , and the purity of magnesium sulfate is further improved through the adsorption of porous graphene.

Benefits of technology

High purity preparation of magnesium sulfate is achieved, ensuring that the purity of the product reaches ≥99.98%, while avoiding the loss of magnesium sulfate during adsorption.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the field of chemical product preparation, and particularly relates to a method for preparing high-purity magnesium sulfate. The present application prepares a porous graphene film with high adsorption capacity by grinding, calcining and immersing dolomite in a magnesium chloride solution, and purifies the magnesium sulfate by using laser processing and plasma etching technology. The present application is to solve the problem that the magnesium sulfate prepared from dolomite as a raw material in the prior art contains impurities such as calcium and iron, and the purity is low, which cannot meet the high purity requirements of downstream industries. The present application provides a method for preparing high-purity magnesium sulfate. The present application uses laser processing to generate graphene on a polyimide sheet, which plays an adsorption role in the process of preparing magnesium sulfate from magnesium oxide, which not only ensures the purity of the obtained magnesium sulfate product, but also ensures that the magnesium sulfate product is not lost during adsorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical product preparation, and particularly relates to a method for preparing high-purity magnesium sulfate. Background Art

[0002] Magnesium sulfate is an inorganic salt consisting of one magnesium ion and one sulfate ion. It is a colorless crystal or white powder at room temperature and has good water solubility. Magnesium sulfate has a variety of hydrate forms, the most common of which is heptahydrate, also known as Epsom salt, which can be used in medicine and agriculture. Magnesium sulfate has a high solubility in water, which increases with increasing temperature. It loses its crystal water when heated, first turning into a monohydrate, and further heating dehydrates to form anhydrous magnesium sulfate. Anhydrous magnesium sulfate is relatively stable at high temperatures, but may decompose into magnesium oxide and sulfur trioxide under extreme conditions.

[0003] Magnesium sulfate is widely used in the medical field. It can be used as a laxative to help relieve constipation symptoms. Intravenous magnesium sulfate solution is clinically used to treat pregnancy-induced hypertension, preeclampsia and eclampsia. When applied topically, magnesium sulfate solution can be used to treat skin inflammation and swelling. In agriculture, magnesium sulfate is also an important trace element fertilizer. Magnesium is a component of chlorophyll and is essential for plant photosynthesis. Magnesium sulfate can supplement magnesium in the soil and improve the growth environment of crops. In addition, magnesium sulfate is also used to adjust the pH value of the soil, which helps plants better absorb other nutrients. Magnesium sulfate is used in many industrial fields. In the textile industry, it is used as a dye fixative to help dyes adhere better to fabrics. In the papermaking industry, magnesium sulfate is used to adjust the pH value of pulp and as a filler and coating aid. In leather processing, magnesium sulfate is used as a softener and degreasing agent to improve the quality of leather. In addition, magnesium sulfate is also used to make other magnesium salts, such as magnesium hydroxide, magnesium carbonate, etc. In the food industry, magnesium sulfate is sometimes used as a food additive. It can be used as a coagulant in tofu making and as a stabilizer in dairy processing. However, due to its possible side effects in the human body, the use of magnesium sulfate in food is strictly regulated and must comply with the food safety standards of various countries. It can be seen that the demand for high-purity magnesium sulfate in the market is very large.

[0004] Magnesium sulfate can be extracted from natural resources, such as seawater, salt lake water or minerals. These resources are rich in magnesium and other minerals. Pure magnesium sulfate can be obtained through evaporation concentration, precipitation, filtration and other process treatments. Magnesium sulfate can also be prepared by magnesium oxide. Dolomite is a common carbonate mineral, the main components of which are calcium carbonate and magnesium carbonate. Dolomite is first calcined at high temperature, and a decomposition reaction occurs to generate calcium oxide, magnesium oxide and carbon dioxide. It is necessary to separate calcium oxide and magnesium oxide by physical or chemical methods, but it is difficult to completely remove the calcium therein. In addition to the main components, dolomite also contains impurity elements such as iron, silicon, and aluminum. These impurities are partially converted into oxides during the calcination process and enter the final magnesium oxide product, thereby affecting the purity of magnesium sulfate in the process of preparing magnesium sulfate from magnesium oxide. Summary of the invention

[0005] In order to solve the problem that magnesium sulfate prepared from dolomite as raw material in the prior art contains impurities such as calcium and iron, has low purity and cannot meet the high purity requirements of downstream industries, the present application provides a method for preparing high-purity magnesium sulfate. The present application uses laser processing to generate graphene on a polyimide sheet, which plays an adsorption role in the process of preparing magnesium sulfate from magnesium oxide, thereby ensuring the purity of the obtained magnesium sulfate product and ensuring that the magnesium sulfate product is not lost during adsorption.

[0006] The present application provides a method for preparing high-purity magnesium sulfate, comprising the following steps:

[0007] S1, grind and calcine the dolomite, add magnesium chloride solution, then add sodium hydroxide, heat and soak for 30-60min, filter and dry;

[0008] S2, after the reaction furnace is heated to 500°C, the product obtained in S1 is placed in it, and the temperature is raised to 1000°C at a heating rate of 150°C / h to obtain magnesium oxide;

[0009] S3, respectively, using deionized water and alcohol to ultrasonically clean the polyimide sheet, and after drying, using a nanosecond laser to perform laser treatment, with a laser power of 3.0-5.5 W and a scanning speed of 120-200 mm / s to obtain a laser-induced porous graphene film, and then subjecting the film to oxygen plasma etching;

[0010] S4, adding the magnesium oxide obtained in step S2 into water, adding the porous graphene material, and then dropping dilute sulfuric acid into the solution, reacting violently with foam, and stopping the addition of acid when the foam decreases, and then filtering with a filter;

[0011] S5. The solution obtained by filtering S4 is adjusted to pH 5-6 with sulfuric acid, and then heated and concentrated at a temperature of 160-180° C. for 30-60 min, and then dried in an oven at a low temperature of 40-55° C. for 3-4 hours to obtain high-purity magnesium sulfate.

[0012] Furthermore, in step S3, the nanosecond laser has a laser wavelength of 1064 nm, a pulse duration of 10 ns, and a repetition frequency of 800 KHz.

[0013] Furthermore, the oxygen plasma etching in step S3 is performed at a pressure of 0.1 Pa-60 Pa and a power of 1 W-60 W for 60-120 seconds.

[0014] Furthermore, in step S4, the mass ratio of magnesium oxide to water is 1:1-2.

[0015] Furthermore, in step S3, the thickness of the polyimide sheet is 120-180 μm.

[0016] Furthermore, in step S1, after the dolomite is ground to 200-250 mesh, the calcination temperature is 500-800°C, the heating rate is 150-200°C / h, and it is maintained for 1-3 hours, and then the temperature is increased to 900°C-1000°C and maintained for 0.5-1 hour.

[0017] Furthermore, the magnesium chloride solution in step S1 is 0.5 mol / L, the heating temperature is 50-60° C., and sodium hydroxide is added to maintain the pH at 11 during soaking.

[0018] Furthermore, in step S1, the mass ratio of dolomite to magnesium chloride is 1:1-1.5.

[0019] Furthermore, in step S4, the weight ratio of magnesium oxide to porous graphene material is 1:0.01-0.1.

[0020] The beneficial effects of this application are:

[0021] 1. The present application decomposes the carbonate components in dolomite and removes some impurities, especially some calcium and iron elements, by grinding, calcining and soaking in magnesium chloride solution. Grinding dolomite into fine particles increases the surface active sites, which is conducive to subsequent pyrolysis and chemical reactions. High-temperature calcination decomposes the carbonates in dolomite into calcium oxide and magnesium oxide, and releases carbon dioxide. At high temperatures, the magnesium chloride solution can form a more easily separated precipitate with the incompletely decomposed dolomite under alkaline conditions, thereby obtaining magnesium hydroxide. When the pH is 10, magnesium ions can be promoted to form magnesium hydroxide precipitates, while other impurity ions are not easy to form precipitates under this pH condition, thereby achieving preliminary purification. Gradually increasing from 500°C to 1000°C can decompose the residual calcium carbonate and magnesium carbonate to avoid leaving impurities in the final product. The heating rate of 150°C / h ensures a uniform temperature rise and prevents local overheating from causing changes in the structure of magnesium oxide.

[0022] 2. The present application uses laser processing and plasma etching technology to prepare a porous graphene film with high adsorption capacity. By treating a polyimide sheet with a nanosecond laser, a graphene structure can be formed on its surface, which has a large specific surface area and good adsorption performance. By oxygen plasma etching, the structure of the graphene film can be further optimized to improve its ability to adsorb impurities. The large specific surface area of ​​graphene provides a large number of adsorption sites, which can effectively adsorb impurities such as calcium and iron in the solution. The inventor found that when the laser power is 3.0-5.5W, the obtained graphene film has a good adsorption effect on impurities in magnesium sulfate. In fact, when the laser power is greater than 5.5w, the degree of graphitization of the film is better than that of the laser power of 3.0-5.5w, but its ability to adsorb calcium and iron impurities in magnesium sulfate is lower than that of the laser power of 3.0-5.5w. And within this power range, the adsorption capacity of the obtained graphene film for calcium ions is significantly higher than that of magnesium ions, which may be because the hole sites of the above-mentioned graphene film have stronger adsorption of calcium ions.

[0023] 3. The present application adjusts the pH to 5-6 in the final step to prevent magnesium ions from forming precipitation again and ensure the stability of the magnesium sulfate solution. Heating and concentrating at 160-180°C can accelerate the evaporation of water and promote the precipitation of magnesium sulfate crystals, while low-temperature drying can prevent the magnesium sulfate crystals from decomposing or deteriorating at high temperatures and maintain their purity. DETAILED DESCRIPTION

[0024] The technical scheme of the present invention and its effects are further described below by specific examples. The following examples are only used to illustrate the content of the present invention and are not used to limit the protection scope of the present invention. Simple changes made to the present invention by applying the concept of the present invention are all within the scope of the protection claimed by the present invention.

[0025] The equipment used in the preparation method of the present invention can be the well-known equipment in the art. The raw materials used in the present invention are commercially available unless otherwise specified.

[0026] Example 1

[0027] S1. After grinding dolomite to 200 mesh, calcining temperature is 800℃, heating rate is 200℃ / h, keep for 1 hour, then heating to 1000℃, keep for 0.5 hour, adding 0.5mol / L magnesium chloride solution after cooling, the mass ratio of dolomite to magnesium chloride is 1:1, then adding sodium hydroxide to adjust pH to 11, heating to 50℃, soaking for 60min, filtering and drying;

[0028] S2, after the reaction furnace is heated to 500°C, the product obtained in S1 is placed in it, and the temperature is raised to 1000°C at a heating rate of 150°C / h to obtain magnesium oxide;

[0029] S3, respectively, using deionized water and alcohol ultrasonic cleaning of a polyimide sheet with a thickness of 120 μm, and after drying, using a nanosecond laser for laser treatment, the nanosecond laser laser wavelength is 1064 nm, the pulse duration is 10 ns, the repetition frequency is 800 kHz, the laser power is 3.0 W, and the scanning speed is 120 mm / s to obtain a laser-induced porous graphene film, and then the film is subjected to oxygen plasma etching at a pressure of 0.1 Pa and a power of 60 W for 60 seconds;

[0030] S4, adding 100 g of magnesium oxide obtained in step S2 to water, with a weight ratio of magnesium oxide to water of 1:1, then adding 1 g of the porous graphene material obtained in step S3, and then dropping dilute sulfuric acid into the solution, reacting violently with foam, and stopping the addition of acid when the foam decreases, and then filtering;

[0031] S5. The solution obtained by filtering S4 was adjusted to pH 5 with sulfuric acid, and then heated and concentrated at 160° C. for 60 min. The solution was then dried in an oven at a low temperature at 40° C. for 4 hours to obtain 258.56 g of high-purity magnesium sulfate with a purity of ≥99.98%.

[0032] Example 2

[0033] S1. After grinding dolomite to 250 mesh, calcining temperature is 500℃, heating rate is 150℃ / h, keep for 3 hours, then heat to 900℃, keep for 1 hour, add 0.5mol / L magnesium chloride solution after cooling, the mass ratio of dolomite to magnesium chloride is 1:1.5, then add sodium hydroxide to adjust pH to 11, heat to 60℃, soak for 30min, filter and dry;

[0034] S2, after the reaction furnace is heated to 500°C, the product obtained in S1 is placed in it, and the temperature is raised to 1000°C at a heating rate of 150°C / h to obtain magnesium oxide;

[0035] S3, respectively, using deionized water and alcohol to ultrasonically clean a polyimide sheet with a thickness of 180 μm, and after drying, using a nanosecond laser for laser treatment, the nanosecond laser has a laser wavelength of 1064 nm, a pulse duration of 10 ns, a repetition frequency of 800 kHz, a laser power of 5.5 W, and a scanning speed of 200 mm / s to obtain a laser-induced porous graphene film, and then the film is subjected to oxygen plasma etching at a pressure of 60 Pa and a power of 1 W for 120 seconds;

[0036] S4, adding 100 g of magnesium oxide obtained in step S2 to water, with a weight ratio of magnesium oxide to water of 1:1.5, then adding 10 g of the porous graphene material obtained in step S3, and then dropping dilute sulfuric acid into the solution, reacting violently with foam, and stopping the addition of acid when the foam decreases, and then filtering;

[0037] S5. The solution obtained by filtering S4 was adjusted to pH 6 with sulfuric acid, and then heated and concentrated at 180° C. for 30 min. The solution was then dried in an oven at a low temperature of 55° C. for 3 hours to obtain 259.72 g of high-purity magnesium sulfate with a purity of ≥99.98%.

[0038] Example 3

[0039] S1. After grinding dolomite to 220 mesh, calcining temperature is 700℃, heating rate is 180℃ / h, keep for 2 hours, then heating to 950℃, keep for 1 hour, adding 0.5mol / L magnesium chloride solution after cooling, the mass ratio of dolomite to magnesium chloride is 1:1.2, then adding sodium hydroxide to adjust pH to 11, heating to 55℃, soaking for 40min, filtering and drying;

[0040] S2, after the reaction furnace is heated to 500°C, the product obtained in S1 is placed in it, and the temperature is raised to 1000°C at a heating rate of 150°C / h to obtain magnesium oxide;

[0041] S3, respectively, using deionized water and alcohol ultrasonic cleaning of a polyimide sheet with a thickness of 160 μm, and after drying, using a nanosecond laser for laser treatment, the nanosecond laser laser wavelength is 1064 nm, the pulse duration is 10 ns, the repetition frequency is 800 kHz, the laser power is 4.0 W, and the scanning speed is 160 mm / s to obtain a laser-induced porous graphene film, and then the film is subjected to oxygen plasma etching at a pressure of 40 Pa and a power of 30 W for 80 seconds;

[0042] S4, adding 100 g of magnesium oxide obtained in step S2 to water, with a weight ratio of magnesium oxide to water of 1:2, then adding 5 g of the porous graphene material obtained in step S3, and then dropping dilute sulfuric acid into the solution, reacting violently with foam, and stopping the addition of acid when the foam decreases, and then filtering;

[0043] S5. The solution obtained by filtering S4 was adjusted to pH 6 with sulfuric acid, and then heated and concentrated at 170°C for 50 min. The solution was then dried in an oven at a low temperature at 55°C for 3 hours to obtain 256.88 g of high-purity magnesium sulfate with a purity of ≥99.98%.

[0044] Comparative Example 1

[0045] S1. After grinding dolomite to 250 mesh, calcining temperature is 500℃, heating rate is 150℃ / h, keep for 3 hours, then heat to 900℃, keep for 1 hour, add 0.5mol / L magnesium chloride solution after cooling, the mass ratio of dolomite to magnesium chloride is 1:1.5, then add sodium hydroxide to adjust pH to 11, heat to 60℃, soak for 30min, filter and dry;

[0046] S2, after the reaction furnace is heated to 500°C, the product obtained in S1 is placed in it, and the temperature is raised to 1000°C at a heating rate of 150°C / h to obtain magnesium oxide;

[0047] S3, respectively, using deionized water and alcohol ultrasonic cleaning of a polyimide sheet with a thickness of 180 μm, and after drying, using a nanosecond laser for laser treatment, the nanosecond laser laser wavelength is 1064 nm, the pulse duration is 10 ns, the repetition frequency is 800 kHz, the laser power is 2.5 W, and the scanning speed is 200 mm / s to obtain a laser-induced porous graphene film, and then the film is subjected to oxygen plasma etching at a pressure of 60 Pa and a power of 1 W for 120 seconds;

[0048] S4, adding 100 g of magnesium oxide obtained in step S2 to water, with a weight ratio of magnesium oxide to water of 1:1.5, then adding 10 g of the porous graphene material obtained in step S3, and then dropping dilute sulfuric acid into the solution, reacting violently with foam, and stopping the addition of acid when the foam decreases, and then filtering;

[0049] S5. The solution obtained by filtering S4 was adjusted to pH 6 with sulfuric acid, and then heated and concentrated at 180° C. for 30 min. The solution was then dried in an oven at a low temperature of 55° C. for 3 hours to obtain 238.46 g of magnesium sulfate with a purity of 97.5%.

[0050] Comparative Example 2

[0051] S1. After grinding dolomite to 250 mesh, calcining temperature is 500℃, heating rate is 150℃ / h, keep for 3 hours, then heat to 900℃, keep for 1 hour, add 0.5mol / L magnesium chloride solution after cooling, the mass ratio of dolomite to magnesium chloride is 1:1.5, then add sodium hydroxide to adjust pH to 11, heat to 60℃, soak for 30min, filter and dry;

[0052] S2, after the reaction furnace is heated to 500°C, the product obtained in S1 is placed in it, and the temperature is raised to 1000°C at a heating rate of 150°C / h to obtain magnesium oxide;

[0053] S3, respectively, using deionized water and alcohol ultrasonic cleaning of a polyimide sheet with a thickness of 180 μm, and after drying, using a nanosecond laser for laser treatment, the nanosecond laser laser wavelength is 1064 nm, the pulse duration is 10 ns, the repetition frequency is 800 kHz, the laser power is 7.0 W, and the scanning speed is 200 mm / s to obtain a laser-induced porous graphene film, and then the film is subjected to oxygen plasma etching at a pressure of 60 Pa and a power of 1 W for 120 seconds;

[0054] S4, adding 100 g of magnesium oxide obtained in step S2 to water, with a weight ratio of magnesium oxide to water of 1:1.5, then adding 10 g of the porous graphene material obtained in step S3, and then dropping dilute sulfuric acid into the solution, reacting violently with foam, and stopping the addition of acid when the foam decreases, and then filtering;

[0055] S5. The solution obtained by filtering S4 was adjusted to pH 6 with sulfuric acid, and then heated and concentrated at 180° C. for 30 min. The solution was then dried in an oven at a low temperature at 55° C. for 3 hours to obtain 239.58 g of magnesium sulfate with a purity of 98.0%.

[0056] Comparative Example 3

[0057] S1. After grinding dolomite to 200 mesh, calcining temperature is 800℃, heating rate is 200℃ / h, keep for 1 hour, then heating to 1000℃, keep for 0.5 hour, adding 0.5mol / L magnesium chloride solution after cooling, the mass ratio of dolomite to magnesium chloride is 1:1, then adding sodium hydroxide to adjust pH to 11, heating to 50℃, soaking for 60min, filtering and drying;

[0058] S2, after the reaction furnace is heated to 500°C, the product obtained in S1 is placed in it, and the temperature is raised to 1000°C at a heating rate of 150°C / h to obtain magnesium oxide;

[0059] S3, adding 100g of magnesium oxide obtained in step S2 to water, with a weight ratio of magnesium oxide to water of 1:1, then adding 1g of graphene produced by Suzhou Carbon Graphene Technology Co., Ltd., and then dropping dilute sulfuric acid into the solution, reacting violently with foam, stopping the addition of acid when the foam decreases, and then filtering;

[0060] S5. The solution obtained by filtering S4 was adjusted to pH 5 with sulfuric acid, and then heated and concentrated at 160° C. for 60 min. The solution was then dried in an oven at a low temperature at 40° C. for 4 hours to obtain 258.72 g of magnesium sulfate with a purity of 96.4%.

[0061] Compared with Example 2, the laser power of step S3 is reduced in Comparative Example 1, and the laser power of step S3 is increased in Comparative Example 2 compared with Example 2. Compared with Example 1, Comparative Example 3 does not use a graphene film obtained by laser-processing a polyimide sheet. It can be seen that the purity of the magnesium sulfate obtained in Comparative Example 1 and Comparative Example 2 is slightly lower, but the yield is greatly reduced, and the purity of the magnesium sulfate obtained in Comparative Example 3 is lower, and the graphene used in Comparative Example 3 is difficult to separate by filtration, so although the graphene can be adsorbed, it reduces the purity of the magnesium sulfate.

Claims

1. A method for preparing high-purity magnesium sulfate, characterized in that The following steps are involved: S1, grind and calcine the dolomite, add magnesium chloride solution, then add sodium hydroxide, heat and soak for 30-60min, filter and dry; S2, after the reaction furnace is heated to 500°C, the product obtained in S1 is placed in it, and the temperature is raised to 1000°C at a heating rate of 150°C / h to obtain magnesium oxide; S3, respectively, using deionized water and alcohol to ultrasonically clean the polyimide sheet, and after drying, using a nanosecond laser to perform laser treatment, with a laser power of 3.0-5.5 W and a scanning speed of 120-200 mm / s to obtain a laser-induced porous graphene film, and then subjecting the film to oxygen plasma etching; S4, adding the magnesium oxide obtained in step S2 into water, adding the porous graphene material, and then dropping dilute sulfuric acid into the solution, reacting violently with foam, and stopping the addition of acid when the foam decreases, and then filtering with a filter; S5. The solution obtained by filtering S4 is adjusted to pH 5-6 with sulfuric acid, and then heated and concentrated at a temperature of 160-180° C. for 30-60 min, and then dried in an oven at a low temperature of 40-55° C. for 3-4 hours to obtain high-purity magnesium sulfate.

2. The method for preparing high-purity magnesium sulfate according to claim 1, characterized in that: The nanosecond laser in step S3 has a laser wavelength of 1064 nm, a pulse duration of 10 ns, and a repetition frequency of 800 KHz.

3. The method for preparing high-purity magnesium sulfate according to claim 1, characterized in that: The oxygen plasma etching in step S3 is performed at a pressure of 0.1 Pa-60 Pa and a power of 1 W-60 W for 60-120 seconds.

4. The method for preparing high-purity magnesium sulfate according to claim 1, characterized in that: In step S4, the mass ratio of magnesium oxide to water is 1:1-2.

5. The method for preparing high-purity magnesium sulfate according to claim 1, characterized in that: The thickness of the polyimide sheet in step S3 is 120-180 μm.

6. The method for preparing high-purity magnesium sulfate according to claim 1, characterized in that: Step S1: After the dolomite is ground to 200-250 mesh, the calcination temperature is 500-800°C, the heating rate is 150-200°C / h, and it is maintained for 1-3 hours, and then the temperature is increased to 900°C-1000°C and maintained for 0.5-1 hour.

7. The method for preparing high-purity magnesium sulfate according to claim 1, characterized in that: In step S1, the magnesium chloride solution is 0.5 mol / L, the heating temperature is 50-60° C., and sodium hydroxide is added to maintain the pH at 11 during immersion.

8. The method for preparing high-purity magnesium sulfate according to claim 1, characterized in that: In step S1, the mass ratio of dolomite to magnesium chloride is 1:1-1.

5.

9. The method for preparing high-purity magnesium sulfate according to claim 1, characterized in that: In step S4, the weight ratio of magnesium oxide to porous graphene material is 1:0.01-0.1.

Citation Information

Patent Citations

  • Method for preparing high-purity magnesium sulfate

    CN101885498A

  • Method for preparing magnesia for magnesium cement by using bischofite and dolomite

    CN102502724A